The Polyfunctuanality In The Names Of Newspapers And Magazines - R. Muhametzyanova, Liliya (2017)
The rapid growth in the number of newspapers and magazines in the communicative space of Russia at the end of the 20th century and the beginning of the 21st century, caused by civilizational, economic, cultural and communication processes. This poses the task of scientific coverage of the nomination problem of periodicals, including the private task of establishing the role of the newspaper and magazine names in the communication processes. The authors solve this task based on two fundamental theses. First, the article highlights the antinomical communicative status of the names of newspapers and magazines. In the processes of communicative interaction, the title of a periodical can be used in isolation from the whole text of a newspaper or magazine and be relatively independent, i.e. autosemantic. Thus, in the combined catalogs of printed periodicals, in the process of verbal or text communication, when it is necessary to point to a specific media publication, the name of periodical is used as a self-sufficient sign.